Mortality of workers at acetylene production plants. - Newhouse, M L (1988)
To reduce the risk of explosion oxyacetylene cylinders are filled with a spongy mass, acetone is added to saturate the mass, and acetylene is pumped into the cylinder. The first cylinders manufactured before 1936 used a kapok filling topped off with about 16 oz of crocidolite asbestos, with a metal gauze thimble inserted to reduce risk of flash back. Cylinders must be examined annually. The use of crocidolite ceased in 1972 and other fillings have been adopted since 1970; kapok cylinders now constitute less than 5% of the total stock. To assess possible hazards, a mortality study of workers first employed between 1935 and 1975 and followed up to December 1984 was undertaken. Simulation tests showed low concentrations of asbestos in the air even in the earliest period. The population studied consisted of 370 workers at the Bilston plant in the West Midlands, 611 at the 14 other plants in England and Wales, and 120 in Scotland. No deaths occurred from mesothelial tumours but there was an excess of deaths from cancer, particularly lung cancer, cancer of the stomach, and cancer of the pancreas, the latter accounting for eight deaths. Risks appeared to be concentrated at the Bilston plant. The importance of these findings is discussed.